The D ~ Sense ex-vivo viability assay application in a patient with stage IV lung adenocarcinoma: a case report - Yu Zhang; Xiaoyuan Wu; Ping He; Jieyu Wu; Xia Gu; Matyas Bendek; Rita Ötvös; Laszlo Szekely (Journal of Medical Case Reports, 2023)
Abstract Background The treatment resistance is a problem for lung cancer. In this study, we used a vitro tissue culturing system to select a new therapy strategy for a patient with tyrosine kinase inhibitors (TKIs) resistance. Case presentation A 42-year-old male Asian patient was diagnosed with advanced lung adenocarcinoma harboring an exon 19 deletion in the epidermal growth factor receptor (EGFR) gene. The patient was treated with Gefitinib, resulting in an almost complete remission for over a year. The patient relapsed after 13 months treatment, and received four cycles of chemotherapy. At 20 months, the patient had developed multiple lung metastases and a solitary cerebellar metastasis. An EGFR T790M mutation was identified in the peripheral blood sample. Subsequent treatment with Osimertinib resulted in a complete response of the intracranial metastasis. By 33 months, the patient had developed a mediastinal tumor mass that responded well to local radiotherapy. By 39 months, an EGFR C797S cis-mutation had been identified and the patient was treated with Brigatinib and Cetuximab. By 44 months, the tumor cells from the pleural effusion had been tested for sensitivity against 30 targeted and cytostatic drugs using the D ~ Sense ex-vivo viability assay. The assay identified 8 drugs with moderate to high sensitivity. Combination therapy of Gemcitabin and Lobaplatin had resulted in disease stabilization. Conclusions The case showed that individualized treatment aided by D ~ Sense ex-vivo viability assay can be a viable option for patients with advanced lung adenocarcinoma with pleural effusions.